Pengaruh Edukasi Gizi terhadap Tingkat Pengetahuan dan Sikap Membaca Informasi Nilai Gizi (Nutrition Facts) Siswa: Studi Quasi Eksperimental - Sesiana Damar Djati; Laeli Nur Hasanah (Jurnal Sehat Mandiri, 2026)
Nutritional knowledge and the habit of reading nutrition facts play an important role in shaping healthy and balanced dietary consumption patterns. However, students’ awareness of reading nutrition information remains relatively low, including at SMP N 1 Jetis Bantul Yogyakarta. This study aimed to analyze the effect of nutrition education on improving students’ knowledge and attitudes toward reading nutrition facts. The study used a quasi-experimental design with a one group pre-post test approach involving 89 students. Nutrition education was delivered through materials on nutrition information using PowerPoint, animated videos, and leaflets. Data were collected using knowledge and attitude questionnaires before and after the intervention and were analyzed using a paired t-test. The results showed a significant increase in students’ knowledge from a mean score of 67.6 to 77, representing an improvement of 9.4 points (p<0.05). Attitudes toward reading nutrition facts also increased from 73.1 to 77.7, an improvement of 4.6 points (p<0.05). Conclusion: nutrition education is effective in improving students’ understanding and awareness in supporting healthy eating habits; therefore, integrating nutrition education into school curricula is recommended as an early preventive strategy.